Strengthening Collaboration Instruments in Stunting Prevention as Implementing the Sustainable Development Goals in Malang Regency East Java - Haryo Prasodjo; Najamuddin Khairur Rijal; Mohd. Agoes Aufiya; Hutri Agustino (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
Sustainable Development Goals prepared by the United Nations in order to improve the welfare of people throughout the world. Of the seventeen priority programs, one of them is related to anti-poverty, anti-hunger targets and the availability of healthy and adequate sanitation. These three programs are often identified with the problem of stunting. In 2022, there will be at least 16 regencies/cities in East Java Province that will be priority areas for working on stunting and one of them is Malang Regency. Therefore, this community service aims to contribute to efforts to deal with stunting through strengthening collaboration between actors. This service partner is the Population Control and Family Planning Service the leading sector for handling stunting in Malang Regency. This community service method consists of four stages, starting from observation and documentation, followed by FGD and workshop activities, monitoring and evaluation and termination. The result of this community service is to contribute to strengthening collaboration instruments for stunting prevention in Malang Regency through the formation of cross-sectoral teams to empowering local communities